USING STATED PREFERENCE DATA TO EXPLORE THE FACTORS AFFECTING TOURISTS’ CRUISE VACATION PREFERENCES - CHAANG IUAN HO (ASEAN Journal on Hospitality and Tourism, 2005)
This study aims to identify the factor that affect tourists’ preferences regarding cruising between Taiwan and its minor islands. To some extent, such cruise serve as a hypothetical travel product. A stated preference technique is employed and two-stage surveys are conducted to collect the tourist’s preference data. A binary logit model is then used to determine individuals’ preferences in relation to cruises and to estimate the parameters. The factors found to affect the tourist’s preferences in relation to cruises are the tourists’ perceptions of cruises, as well as the service attributes of the cruises, including self-independence in tour arrangements and the comfort/convenience derived from traveling in this way, the relatively long duration of the journey (4 days), the free or partial-subsidized on-shore excursions and the on-board recreational activities. However, the socio-demographic variables are not found to significantly affect tourist’s preferences for cruises.